2021
DOI: 10.1016/j.chaos.2020.110438
|View full text |Cite
|
Sign up to set email alerts
|

Optimal control approach of a mathematical modeling with multiple delays of the negative impact of delays in applying preventive precautions against the spread of the COVID-19 pandemic with a case study of Brazil and cost-effectiveness

Abstract: Highlights We propose to study an optimal control approach with delay in state and control variables. Numerical simulation of different strategies. The cost of effectivness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 20 publications
0
29
0
Order By: Relevance
“…For the adjoint equations and transversality conditions can be obtained by using Pontryagin’s maximum principle [38] , [39] , [40] , [41] such that …”
Section: The Optimal Control: Existence and Characterizationmentioning
confidence: 99%
“…For the adjoint equations and transversality conditions can be obtained by using Pontryagin’s maximum principle [38] , [39] , [40] , [41] such that …”
Section: The Optimal Control: Existence and Characterizationmentioning
confidence: 99%
“…Recent studies reported that between 2 and 14 days can elapse from the day of SARS-CoV-2 infection and the appearance of the first disease symptoms (incubation period) (Kouidere et al 2020;Lee et al 2020;Huang et al 2020). Thus, if SARS-CoV-2 were transported in particulate material, an increase of infection cases should be observed after contamination events.…”
Section: Effect Of Meteorological Parameters On Pm 25 and Pm 10mentioning
confidence: 99%
“…A new proposed model is given in [ 9 ] to simulate the new cases and deaths of the virus outbreak in India. The study of the virus impact in Brazil through a multiple-delay mathematical model and the optimal control strategies is illustrated in [ 10 ]. Other relative studies of integer-order models can be found in [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%